Experimental Study on the Performance of a Four-Stroke Spark-Ignition Engine Using Pertalite–Bioethanol Fuel Blends - Indra Hermawan; Darianto; Saturnus Wardiman Gulo (Universitas Medan Area, 2026)
The energy crisis and environmental impacts of fossil fuels have prompted the search for alternative fuels such as bioethanol. This study analyzes the performance of a 4-stroke gasoline engine using pure Pertalite (100%) and bioethanol blends (25% and 35%) through experimental testing with a dynamometer. The evaluated parameters include power, torque, and specific fuel consumption (SFC). The results show that pure Pertalite delivers the best performance, with a maximum power of 8.00 kW and peak torque of 10.30 Nm within the 3000–6000 rpm range. The 25% bioethanol blend produced higher power (7.30 kW) compared to the 35% blend (7.10 kW) at higher speeds (7000–9000 rpm), although both remain below Pertalite. Pertalite also exhibited the most efficient SFC (522.84–697.13 g/kWh), followed by 25% bioethanol (808.05–1371.80 g/kWh) and 35% bioethanol (2160.00–5760.00 g/kWh), particularly at lower engine speeds. Increasing the bioethanol content beyond 25% significantly reduced engine performance due to its lower energy content and suboptimal combustion characteristics. Nevertheless, a 25% bioethanol blend may be considered an environmentally friendly alternative with acceptable efficiency trade-offs. These findings highlight the importance of optimizing bioethanol composition to balance engine performance and sustainability, as well as the need for further research on emissions and material durability.